Wastewater Treatment for struvite production: A bibliometric study (Research, Society and Development, 2018)
Researches focused in showing solutions for the waste disposal in effluents have been targeted for presenting the possibility of combining cost-effective and environmentally viable solutions. Its application for obtaining a substance called struvite is the goal of many recent researches, fact that leads to the objective of this research, which proposes presenting processes to select relevant articles to the theme “wastewater treatment for struvite production” in the Web of Science database, in order to create a portfolio of bibliographic references on the subject in question. The whole process leads to the selection of 20 relevant articles, aligned with the theme and arranged in several areas of activity. In addition, a bibliometric analysis of the portfolio was carried out, in order to characterize and analyze the selected articles. Finally, an evaluation of the future research trends has been made, highlighting its positive and negative factors, through a SWOT matrix.